JASA LINGKUNGAN TAMAN KEANEKARAGAMAN HAYATI (KEHATI) BADAN LINGKUNGAN HIDUP DI KABUPATEN SEKADAU TAHUN 2017 - Desiana, .; Roslinda, Emi; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2019)
Environmental services are the services provided by the ecosystem functions that have direct and indirect benefits. The purpose of this study is to describe the potential of environmental services in the KEHATI Park, Sekadau Regency. KEHATI Park Sekadau was built in 2012 with the aim of adding green open space land cover, collection of plants, development of science and ecotourism and the sources of seeds. The KEHATI Park ecosystem in Sekadau Regency has the potential of environmental services as a result of the interaction of the ecosystem in it. The Millennium Ecosystem Assessment (MEA 2005) classifies environmental services into four namely provisioning services, regulating services, cultural services, and supporting services. The method used is the survey method with interview techniques and questionnaires. For sampling of respondents conducted by accidental sampling and census. Data analysis was conducted based on MEA (2005) which was then analyzed descriptively. The environmental services contained in the Sekadau Forest Park are potential provisioning services that can be seen from foodstuffs such as fruit plants, medicines, vegetables, and forestry plants. Then regulating services that have the function of maintaining air quality, cultural services which are non-material benefits as a place of recreation, and the existence of supporting services (supporting services).Keywords: Environmental Services, KEHATI Park Sekadau, Millenium Ecosystem AssesmentÂ